Tailoring Civil Service Pay Analysis and Advice to Context : Challenges, Approaches, and the Case of Lao PDR - Barma, Naazneen H.; Orac, Jana (World Bank, Washington, DC, 2014)
The adequacy of compensation for government workers and the affordability of the public sector wage bill are important concerns for many developing countries. Suitable pay is considered a necessary -- albeit far from sufficient -- condition for attracting and retaining skilled public sector staff. This paper makes the case for conducting fine-grained analysis of pay and compensation issues in order to enable an accurate assessment of the challenges faced and thereby to generate good-fit reform recommendations that are both principled and feasible. The first part of the paper focuses on prevalent challenges in pay reform, both contextual and analytical. It builds on the experiences from three very different settings: Armenia, the Lao People s Democratic Republic, and Mongolia. The study begins by surveying some of the common difficulties in conducting granular analysis on civil service compensation. It then outlines a series of methodological approaches that can prove useful in developing comprehensive, targeted, and nuanced pay analyses and discusses how it is possible to overcome potential limitations in practice. The second half of the paper presents a case study of pay and compensation analysis in Lao PDR. The study illuminates how a number of these approaches can be combined in assessing a specific set of pay challenges and generating robust recommendations tailored to context. A brief postscript, with the benefit of hindsight on what subsequently happened on the ground in Lao PDR, reflects on the limitations of technical analysis in motivating reform implementation in practice.